Strategies for the design of domestic pellet boilers - Ribeiro, Pedro (2019)
Domestic and industrial heating are amongst the most attractive applications for biomass as it combines high efficiency and ease-of-use. Boilers and furnaces in this range are usually of simple design and control algorithm while expected to operate over a wide range of thermal loads, typically from up 30% of the nominal load. Such constrainments often limit the overall efficiency of biomass use. In addition, from the manufacturing point of view, a product with flexibility of operation would provide a quasi-universal solution for a wide range of applications. The present paper investigates the influence of the fuel grate dimensions and the heat exchanger design on the thermal efficiency of a 25 kW pellet boiler. The prototype has a controllable independent supply of primary and secondary air and the temperature is monitored at critical locations. The continuous analysis of the flue gases for CO , NOx, O and CO enabled the definition of an operation envelope that resulted in CO emissions as low as 10 ppm, using standard A1 grade pellets as fuel. 2 2